Latin tardif, francais ancien : continuites et ruptures - Carlier, Anne; Guillot-Barbance, Celine (Beihefte zur Zeitschrift fur romanische Philologie, 2018)
Even though a rich written tradition documents the evolution from Latin to French, the crucial transition from Late Latin to Old French in the oral language remains partially obscure. Thanks to a corpus-based approach and the collaboration of Latinists and French historians, this edited volume sheds a new light on this "missing link".